Cas9 editing of ATXN1 in a spinocerebellar ataxia type 1 mice and human iPSC-derived neurons - Kelly J. Fagan; Guillem Chillon; Ellie M. Carrell; Elisa A. Waxman; Beverly L. Davidson (Elsevier, 2024)
Spinocerebellar ataxia type 1 (SCA1) is an adult-onset neurodegenerative disease caused by an expansion of the CAG repeat region of the ATXN1 gene. Currently there are no disease-modifying treatments; however, previous work has shown the potential of gene therapy, specifically RNAi, as a potential modality. Cas9 editing offers potential for these patients but has yet to be evaluated in SCA1 models. To test this, we first characterized the number of transgenes harbored in the common B05 mouse model of SCA1. Despite having five copies of the human mutant transgene, a 20% reduction of ATXN1 improved behavior deficits without increases in inflammatory markers. Importantly, the editing approach was confirmed in induced pluripotent stem cell (iPSC) neurons derived from patients with SCA1, promoting the translatability of the approach to patients.